Creativity in Utilization Nipa Waste for Environmental Sustainability and Family Economic Improvement - Khoffifah, Khoffifah; Lisdawati, Lisdawati; Kresnina, Kresnina; Sagena, Uni (STMIK Widya Cipta Dharma, 2024)
Waste management can be achieved through reduction strategies or direct handling of waste. In fostering creativity, utilizing nipa waste represents an innovative effort to support environmental sustainability and enhance the local economy. Environmental well-being encompasses both health and cleanliness, as a clean environment forms the foundation of a healthy life. However, public awareness of maintaining environmental cleanliness remains low, and habits of neglect continue to prevail in daily life. Beyond achieving improved cleanliness, creative initiatives such as nipa waste utilization also inspire innovation and fresh ideas. This study explores the potential of nipa waste as an alternative raw material to reduce negative environmental impacts while providing economic benefits for the local community in Samarinda Seberang. The research employs qualitative methods, including literature reviews, field surveys, and data analysis of nipa waste utilization processes. The results indicate that utilizing nipa waste can significantly contribute to environmental sustainability by recycling organic waste into value-added products. Furthermore, it creates economic opportunities for the local community through new businesses and increased income. The discussion highlights the implications of these findings for environmental sustainability and emphasizes the potential for collaboration among the government, community, and private sector in promoting nipa waste utilization. The study concludes by underscoring the importance of nipa waste utilization as a holistic approach to achieving sustainable environmental management and generating positive economic impacts for the local community in Samarinda Seberang.